Pelanggaran Etika Bisnis dalam Eksploitasi Tenaga Kerja di Industri Fashion Global Merek Shein - Berlian Selvia; Aurelle Latisha Hardana; Mohamad Zein Saleh (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The global fashion industry has experienced rapid growth, driven by a business model that prioritizes fast production and affordable prices. However, this success is often built on labor exploitation practices, as seen in Shein, a global retail company from China. An investigation by Public Eye revealed violations regarding excessive working hours and inadequate wage payments within the company’s supply chain. This study aims to analyze the business ethics violations in Shein’s labor practices, the impacts on workers and the supply chain, and provide recommendations for improvement. The research was conducted using a qualitative method based on literature review. The findings indicate violations of business ethics principles and applicable international labor standards. The recommendations include implementing stricter supervision, operational transparency, and enhancing workers' welfare. This research contributes significantly to encouraging the adoption of more responsible and sustainable business practices.